2016
DOI: 10.3892/ol.2016.5295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma microRNA levels to predict insensitivity of patients with advanced lung adenocarcinomas to pemetrexed and platinum

Abstract: Abstract. Pemetrexed combined with platinum is a first-line therapy used to treat patients with advanced non-small cell lung cancer (NSCLC) that exhibit negative or unknown epidermal growth factor receptor (EGFR) mutational status or anaplastic lymphoma kinase (ALK) rearrangements. Lung adenocarcinoma (LAC) is the primary type of NSCLC. In order to prevent overtreatment, it is necessary to identify patients with LAC who may not benefit from certain chemotherapies. Patients recruited in the present study (n=129… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Zhu et al (2016) on 129 participants, it was noticed that miR-25, miR-21, miR-27b and miR-326 can consider as the most promising biomarker for LAC (J. Zhu et al, 2016). MiR-326 upregulates epithelial-to-mesenchymal transition (EMT)-induced cells invasion in LAC by targeting of ADAM17 (Cai et al, 2015).…”
Section: Lung Cancermentioning
confidence: 99%
“…Zhu et al (2016) on 129 participants, it was noticed that miR-25, miR-21, miR-27b and miR-326 can consider as the most promising biomarker for LAC (J. Zhu et al, 2016). MiR-326 upregulates epithelial-to-mesenchymal transition (EMT)-induced cells invasion in LAC by targeting of ADAM17 (Cai et al, 2015).…”
Section: Lung Cancermentioning
confidence: 99%
“…Finally, miR-21 is up-regulated not only in HCC but also in precursor lesions. It has been previously reported that miR-21 is up-regulated in HCC tissues and hepatoma cell lines, 29,37 and that its expression gradually increases along with an augmented invasive phenotype of the tumor. Moreover, miR-21 has been reported to play a role in hepatocyte proliferation by promoting cyclin D1 translation and inhibition of tumor suppressor genes (eg, phosphatase and tensin homolog) and apoptotic genes (programed cell death 4 and B-cell lymphoma 2).…”
Section: Discussionmentioning
confidence: 98%
“…Also, miR-483-3p reversed EMT and repressed migration, invasion, and metastasis of GR NSCLC cells. Mechanistically, miR-483-3p directly targeted integrin β3, consequently inhibiting the downstream FAK/Erk signaling pathway, highlighting miR-483-3p is a prospective target for combination treatment to overcome acquired EGFR TKI resistance in EGFR-mutant NSCLC [226,227]. miR-625-3p can potentially target AXL receptor tyrosine kinase, and this miRNA expression is markedly decreased in the HCC827GR cell line, while its overexpression partly reversed gefitinib resistance.…”
Section: Gefitinibmentioning
confidence: 99%